Safety of coitally administered tenofovir 1% gel, a vaginal microbicide, in chronic hepatitis B virus carriers: Results from the CAPRISA 004 trial - BAXTER, Cheryl (2013)
Tenofovir disoproxil fumarate, a licensed oral treatment for both HIV and Hepatitis B virus (HBV) infections, has been associated with severe rebound hepatic flares when treatment is interrupted. A gel formulation of tenofovir is currently being assessed as a microbicide against HIV. If licensed, it is possible that tenofovir gel could be used either intentionally or unintentionally by HBV carriers. The purpose of this study was to establish the safety of tenofovir gel use in this patient group participating in the CAPRISA 004 tenofovir gel trial. HBV infection status was assessed at enrolment and study exit. Liver function testing was performed at enrolment, study months 3, 12, 24, study exit, and two months after exiting the study. At enrolment, 34 women were identified as being HBV carriers and 22 women acquired HBV infections during follow-up; 14 and 8 in the tenofovir and placebo gel arms respectively (p=0.21). Intermittent tenofovir gel use did not cause an increase in hepatic flares or impact on viral load suppression in women with HBV infection. There were 2 hepatic flares in each gel arm during follow-up and none two months after cessation of gel at study exit. The mean HBV DNA levels were similar at enrolment and exit in both study arms. Tenofovir gel, when used intermittently, was safe to use in women with HBV infection.